Evaluación agronómica, fitosanitaria y productiva de siete líneas de maní (Arachis hypogaea L.) sembradas en la época seca en la zona de Quevedo. - Guamán Anchundia, Robinson Elicier (2013)
The objetive of this research was to determine the agronomic and phytosanitary seven promising lines and four comercial varieties of groundnut (Harachis hypogaea L.) planted in the dry season in the area of Quevedo. This work was performed during the 2010 dry season, from September through December at the Experimental Farm property La Maria State Technical University of Quevedo, located at Km. 7.5 via Quevedo - El Empalme, whose geographical coordinates are 79º 30’ 08’’ east longitude and 01º 00’ 35’’ south latitude. Varieties tested: DIAMOND, POLACHI, INIAP-380, INIAP-381; lines : CB-02, CB-05, CB-12, CB-13, CB-15, CB-16, CB-23. Design was used a randomized complete block (BCA) with 11 treatments and 3 repetitions. For some variables phytosanitary averages obtained were integralizados incidence and severity as the area under the curve of disease progression (AACP), as trapezoidal integration equation described by Campbell and Madden (1990). For comparison between treatment means test was used and Ducan’s multiple range at 5% probability of error. To perform these statistical analysis, we used the SAS statistical package available in 9.0 (SAS, 2002). Germination in this experiment was up 72.6% (line CB-12), with a maximum of 84.6 (range DIAMOND). There was no statistical difference between treatments. It is observed that all varieties tested have a higher germination compared with the promising line. The days to flowering showed values between 20.0 (lines CB-15 and CB-16) and 24.7 days (line CB- 05). It was also a significant difference between the treatments. The group of promising lines showed a similar behavior between the materials, plant height, the findings ranged from 35.5 cm to promising line CB-13 and 46.0 cm for the INIAP- 381. Likewise, statistically significan differences among treatments. For the severity (percentage of necrotic area plot “1) per plot of foliar diseases AACPEF given by the comparison of means showed statistically significan difference among treatments, standing with units of area under the INIAP- 380 of 365,6 while the other INIAP- 381 accumulated an average of 1178.3 (Table 6). The average severity of all lines tested, is greater (759.5) than commercial varieties (666.0). In turn, the severity (%) of leaf diseases in plants given by the AACPEF marked, statistically significan differences were found between treatments, with values between 83.3 in the INIAP- 380 and 225.2 units for line CB- 23. The average of the witnesses (commercial varieties) reached 141.3 units, unlike the average of the promising lines (192.2 units). For the number of lesions leaflet leaf disease-1 given by the AACPEF. As in the above variables, here also showed statistically significan difference among the treatments studied, highlighting lower area inits INIAP varieties – 380 and INIAP – 381 with 9.0 and 13.4, respectively, while the another variety POLACHI accumulated an average of 85.8 (table 6). The average severity of all lines evaluated (37.9) versus commercial varieties (37.3) was similar. The number of lesions leaflet-1 of leaf spot ( Cercospora arachidicola and Cercosporidium personatum), was demonstrated statistically significant differences between treatments during the reproductive phenological stages R4 and R5, while in the other. During all stages of germplasm behavior was similar, generally emphasizing the INIAP -380, the same number of lesions had lower folíolo’1. The average values during the last assessment (R7) were between 1.3 (INIAP -380) and 5.1 (CB-23) injuries leaflet-1. This behavior is equally evident in the previous health variables (AACPEF). The fruit yield showed no statistically significant difference between the materials, but the material that stood out in terms of performance was the commercial variety Diamante with 1404.9 kg ha-1, which was a lower production was commercial variety INIAP-380 to 1083.6 kg ha’’1. The colors of the beans (seeds) were among white, red and purple. It is recommended to further evaluate the agronomic characteristics, plant and productive of the best promising lines obtained in the UICYT-UTEQ to in the future to launch is for the central coast of Ecuador. Likewise, research on fertilization, distance, population and chemical control of diseases, with the best promising lines obtained in this experiment compared with commercial varieties on the marked.